The Control of Nonlinear Oscillatory Systems with Delay - Pušenjak, Rudolf; Oblak, Maks (Anali PAZU, 2022)
This paper treats the adaptation of the Extended Lindstedt-Poincare Method with multiple time scales (EL-PM) for analysis of stationary and nonstationary resonances of harmonically excited Duffing oscillator with time delay feedback control. The fundamental and ⅓ subharmonic resonance, respectively of Duffing oscillator with feedback control are analyzed in details. The comparison of stationary resonances with nonstationary resonances due to the slowly varying excitation frequency is presented by means of examples, which are computed by programming tool Mathematica®.
Keywords: Duffing oscillator; time delay feedback control; osnovna in subharmonična resonanca; EL-P method